Simultaneous femtomole determination of cysteine, reduced and oxidized glutathione, and phytochelatin in maize (Zea mays L.) kernels using high-performance liquid chromatography with electrochemical detection - Potesil, David; Petrlova, Jitka; Adam, Vojtech; Vacek, Jan; Klejdus, Borivoj; Zehnalek, Josef; Trnkova, Libuse; Havel, Ladislav; Kizek, Rene (Journal of chromatography. A, 2005)
Thiol compounds such as cysteine (Cys), reduced (GSH) and oxidized (GSSG) gluathione, and phytochelatins (PCs) play an important role in heavy metal detoxification in plants. These thiols are biological active compounds whose function is elimination of oxidative stress in plant cells. The aim of our work was to optimise sensitive and rapid method of high-performance liquid chromatography coupled with electrochemical detector (HPLC-ED) for determination of the abovementioned thiol compounds in maize (Zea mays L.) kernels. New approach for evaluation of HPLC-ED parameters is described. The most suitable isocratic mobile phase for the separation and detection of Cys, GSH, GSSG and PC2 consisted of methanol (MeOH) and trifluoroacetic acid (TFA). In addition, the influence of concentrations of TFA and ratio of MeOH:TFA on chromatographic separation and detection of the thiol compounds were studied. The mobile phase consisting from methanol and 0.05% (v/v) TFA in ratio 97:3 (%; v/v) was found the most suitable for the thiol compounds determination. Optimal flow rate of the mobile phase was 0.18 ml min(-1) and the column and detector temperature 35 degrees C. Hydrodynamic voltammograms of all studied compounds was obtained due to the selection of the most effective working electrodes potentials. Two most effective detection potentials were selected: 780 mV for the GSSG and PC2 and 680 mV for determination of Cys and GSH. The optimised HPLC-ED method was capable to determine femtomole levels of studied compounds. The detection limits (3 S/N) of the studied thiol compounds were for cysteine 112.8 fmol, GSH 63.5 fmol, GSSG 112.2 fmol and PC2 2.53 pmol per injection (5 microl). The optimised HPLC-ED method was applied to study of the influence of different cadmium concentrations (0, 10 and 100 microM Cd) on content of Cys, GSH, GSSG and PC2 in maize kernels. According to the increasing time of Cd treatment, content of GSH, GSSG and PC2 in maize kernels increased but content of Cys decreased. Decreasing Cys concentration probably relates with the increasing GSH and phytochelatins synthesis.
Keywords: Temperature; fytochelatiny; Cysteine; Chromatography, High Pressure Liquid; Metalloproteins; senzitivita a specificita; Seeds; Cadmium; kadmium; semena rostlinná; Reproducibility of Results; glutathiondisulfid; elektrochemie; reprodukovatelnost výsledků; glutathion; Trifluoroacetic Acid; Zea mays; cystein; kyselina trifluoroctová; Phytochelatins; Glutathione Disulfide; metaloproteiny; Sensitivity and Specificity; Glutathione; Electrochemistry; vysokoúčinná kapalinová chromatografie; teplota; kukuřice setá